A systematic review of coach developers` professional learning - Walton, J.; Cushion, C.; Stodter, A.; Cope, E. (Sports Coaching Review, 2024)
The objective of this paper was to systematically review the empirical evidence surrounding sport coach developers` (CDs) professional learning. CDs are key in coaching ecosystems because they influence coaches` learning. However, little is known about the processes and mechanisms involved in how CDs learn to practice, which has implications for their training and support requirements. A thematic synthesis was undertaken on the 30 included studies. Findings generated themes concerning (1) CDs` understanding and application of learning theory, (2) the influence of their employing governing body, (3) the role and importance of peers, and (4) expert facilitators in influencing CDs` professional learning and practice. These findings provide insights for CDs and organisations responsible for training and developing CDs. The limited body of literature highlights the juvenile state of CD research, and recommendations are made to further investigate CDs from a broader range of sports and contexts.